2017
DOI: 10.1002/brb3.650
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal AMPARs involve the central sensitization of rats with irritable bowel syndrome

Abstract: ObjectiveThe roles of hippocampal AMPARs were investigated in irritable bowel syndrome (IBS)‐like rats to clarify the central sensitization mechanisms.Methods IBS model was induced by neonatal maternal separation. The effects of AMPARs on visceral hypersensitivity were examined by the responses of abdominal muscle to colorectal distension after the bilateral intrahippocampal injections of CNQX (an AMPAR inhibitor). The expressions of hippocampal AMPARs (GluR1 and GluR2) were determined by Western blot.ResultsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…Previous studies showed that failure of stress-coping mechanisms in some IBS subsets patients could lead to inadequate neuroendocrine autonomic responses along the HPA, such as altered cortisol levels and increased vagal activation [8, 63, 64]. In this way, their sensory information processing is impaired by the overload of the emotional circuitry, as shown by some sparse studies on functional magnetic resonance imaging in IBS subjects [65] or immunochemistry in animal models [66]. Even more interesting, persistent stress in animal models is shown to morphologically alter hippocampal circuitry and suppress neurogenesis [8], while two recent studies of Mayer and colleagues demonstrate decreased gray matter density in prefrontal cortex, posterior parietal cortex, pregenual anterior cingulate cortex, and similar trends in the posterior insula/secondary somatosensory cortex, (para)hippocampus, regions involved in cognitive functions among others [67].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that failure of stress-coping mechanisms in some IBS subsets patients could lead to inadequate neuroendocrine autonomic responses along the HPA, such as altered cortisol levels and increased vagal activation [8, 63, 64]. In this way, their sensory information processing is impaired by the overload of the emotional circuitry, as shown by some sparse studies on functional magnetic resonance imaging in IBS subjects [65] or immunochemistry in animal models [66]. Even more interesting, persistent stress in animal models is shown to morphologically alter hippocampal circuitry and suppress neurogenesis [8], while two recent studies of Mayer and colleagues demonstrate decreased gray matter density in prefrontal cortex, posterior parietal cortex, pregenual anterior cingulate cortex, and similar trends in the posterior insula/secondary somatosensory cortex, (para)hippocampus, regions involved in cognitive functions among others [67].…”
Section: Discussionmentioning
confidence: 99%
“…MS induces both functional and structural changes in several brain regions including the PFC, hippocampus, amygdala and nucleus accumbens (150,158163) . More specifically, impaired synaptic long-term potentiation, dendritic atrophy as well as reduced dendritic spine density have been reported in the medial PFC and hippocampus of adolescent and adult MS rats (63,68,97,104,116,140,153,158,164171) . By contrast, MS induces dendritic hypertrophy in the amygdala (57) .…”
Section: The Maternal Separation Modelmentioning
confidence: 95%
“…The gabaergic system plays a role in CRF synthesis inhibition in the central amygdala, allowing a buffering of the noradrenergic response to stress. In addition, MS impairs glutamatergic (140142) , serotonergic (48,61,83,143147) , dopaminergic (64,145,148153) , opioidergic (152,154) and endocannabinoidergic (66) transmission. In the central nervous system, serotonin is involved in neuronal development (155) , emotionality and also pain modulation (156,157) .…”
Section: The Maternal Separation Modelmentioning
confidence: 99%
“…Recently, in a rat model of maternal separation-induced IBS associated with alterations of the microbiota homeostasis, bilateral hippocampal injection of the AMPA receptor antagonist, CNQX, reduced visceral pain perception to colorectal distension. In addition, GluA2 receptor levels significantly increased in the hippocampus of IBS-like rats, with respect to controls, both in normal conditions and after high electrical field induced LTP-responses, suggesting a possible involvement of GluA2 subunits in central mechanisms of chronic visceral pain control [195]. Persistence of pain perception in IBS, depends upon changes in afferent neurons and CNS pain processing pathways, leading to chronic visceral hypersensitivity [75].…”
Section: Glutamatergic Dysfunction Along the Microbiota-gut-brain mentioning
confidence: 99%